Penerapan Model Pembelajaran Talking Stick dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam pada Siswa Sekolah Dasar - Desmaniarti Desmaniarti; Azizah Aryati (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
The purpose of Islamic religious education in elementary schools is to develop faith through providing, fertilizing, and developing knowledge and appreciation, experience, habituation and experience of students about Islam so that they become Muslim humans who continue to develop in terms of faith, devotion to Allah SWT. The purpose of this study was to determine how much impact and influence the application of the talking stick learning model in improving the learning outcomes of Islamic religious education in class IV semester I students at SDN 01 Bengkulu Selatan. This research method is Classroom Action Research. This research was conducted at SDN 01 Bengkulu Selatan, the subject of this research amounted to 20 students. The instruments used by researchers in the data collection process used three forms, namely observation, documentation and tests. Data analysis was carried out through observation sheet analysis by calculating the average observation score. The conclusion of the research reveals that the application of the talking stick learning model has an impact on improving the learning outcomes of Islamic religious education, the increase can be seen in terms of increasing student activity and learning outcomes during the learning process. The talking stick learning model tries to optimize student activity